Thyroid in pregnancy: From physiology to screening - Springer, Drahomira; Jiskra, Jan; Limanova, Zdenka; Zima, Tomas; Potlukova, Eliska (Critical reviews in clinical laboratory sciences, 2017)
Thyroid hormones are crucial for the growth and maturation of many target tissues, especially the brain and skeleton. During critical periods in the first trimester of pregnancy, maternal thyroxine is essential for fetal development as it supplies thyroid hormone-dependent tissues. The ontogeny of mature thyroid function involves organogenesis, and maturation of the hypothalamus, pituitary and the thyroid gland; and it is almost complete by the 12th-14th gestational week. In case of maternal hypothyroidism, substitution with levothyroxine must be started in early pregnancy. After the 14th gestational week, fetal brain development may already be irreversibly affected by lack of thyroid hormones. The prevalence of manifest hypothyroidism in pregnancy is about 0.3-0.5%. The prevalence of subclinical hypothyroidism varies between 4 and 17%, strongly depending on the definition of the upper TSH cutoff limit. Hyperthyroidism occurs in 0.1-1% of all pregnancies. Positivity for antibodies against thyroid peroxidase (TPOAb) is common in women of childbearing age with an incidence rate of 5.1-12.4%. TPOAb-positivity may be regarded as a manifestation of a general autoimmune state which may alter the fertilization and implantation processes or cause early missed abortions. Women positive for TPOAb are at a significant risk of developing hypothyroidism during pregnancy and postpartum. Laboratory diagnosis of thyroid dysfunction during pregnancy is based upon serum TSH concentration. TSH in pregnancy is physiologically lower than the non-pregnant population. Results of multiple international studies point toward creation of trimester-specific reference intervals for TSH in pregnancy. Screening for hypothyroidism in pregnancy is controversial and its implementation varies from country to country. Currently, the case-finding approach of screening high-risk women is preferred in most countries to universal screening. However, numerous studies have shown that one-third to one-half of women with thyroid disorders escape the case-finding approach. Moreover, the universal screening has been shown to be more cost-effective. Screening for thyroid disorders in pregnancy should include assessment of both TSH and TPOAb, regardless of the screening approach. This review summarizes the current knowledge on physiology of thyroid hormones in pregnancy, causes of maternal thyroid dysfunction and its effects on pregnancy course and fetal development. We discuss the question of case-finding versus universal screening strategies and we display an overview of the analytical methods and their reference intervals in the assessment of thyroid function and thyroid autoimmunity in pregnancy. Finally, we present our results supporting the implementation of universal screening.
Keywords: Thyroid Diseases; Pregnancy; Humans; nemoci štítné žlázy; Female; Thyroid Gland; screening; lidé; Pregnancy Complications; štítná žláza; pregnancy loss; ženské pohlaví; pregnancy; těhotenství; komplikace těhotenství; hormony štítné žlázy; thyroid-stimulating hormone; anti-thyroperoxidase antibodies; Autoimmune thyroid disease; Thyroid Hormones